Maternal diet shapes infant microbiota and defensive capacity against infections in early life via differential human milk compositionResearch in context - Karla Rio-Aige; Marta Selma-Royo; Raúl Cabrera-Rubio; Sonia González; Cecilia Martínez-Costa; Margarida Castell; María J. Rodríguez-Lagunas; María Carmen Collado; Francisco J. Pérez-Cano (EBioMedicine)
Summary: Background: Maternal nutritional status and dietary profile during pregnancy and lactation have short- and long-term impacts on offspring health. However, there is an incomplete understanding of the mechanisms behind these health effects. This study aims to assess the effect of maternal diet on the health of offspring by examining to unravel the impact of maternal diet on offspring health outcomes and evaluate the link between maternal nutrition, human milk immune components and neonatal colonisation as potential mechanisms that mediate the influence of maternal diet in the incidence of infant infections. Methods: To assess this objective, we used two complementary approaches by which a clinical observational study based on the MAMI birth cohort guided a preclinical interventional analysis using a neonatal rat model of rotavirus-induced gastroenteritis. Findings: The findings in both approaches demonstrated that a maternal diet rich in plant-based protein, fibre and polyunsaturated fatty acids, was linked to reduced incidence and severity of infections in offspring that would be mediated by beneficial modulation of the gut microbiota and immune system. Specifically, in the suckling rats, a predominant Th1 immune response and an enhanced virus-specific response were observed. Moreover, human milk IgA and rat milk IgG2c played a key protective role that complemented the effects of maternal diet. Interpretation: These results strengthen the importance of maternal diet during pregnancy and lactation supporting infant health. Funding: The study was supported by LaMarató-TV3 (DIM-2-ELI, ref. 2018-27/30-31).